Diagnostic and therapeutic implements based on advanced Biotechnology should be available in low-income countries - Bertelli, Matteo; Paolacci, Stefano; Beccari, Tommaso; Dundar, Munis; Sozanski, Gabriella; Miertus, Stanislav; Miertus, Jan; Luzzatto, Lucio (Acta Biomedica Atenei Parmensis, 2019)
N.A.